Розроблення і впровадження процесів безперервної інтеграції та розгортання для програмних проектів - Чайківський, Павло Остапович; Chaikivskyi, Pavlo Ostapovych (Національний університет "Львівська політехніка", 2024)
Об’єкт дослідження – процеси CI/CD в життєвому циклі розробки ПЗ. Мета роботи – розробка та демонстрація функціональної CI/CD системи для автоматизації доставки інфраструктури та додатку з використанням Azure DevOps та інфраструктури як коду. Методи – аналіз літератури, системний аналіз, порівняння технологій, проектування, моделювання, реалізація, тестування. Проаналізовано методології DevOps, CI/CD, хмарні технології Azure, інструменти Azure DevOps та Terraform. Розроблено та реалізовано два CI/CD конвеєри: для розгортання інфраструктури та для збірки/розгортання .NET Core додатку на різні середовища. Проведено аналіз ефективності, безпеки, визначено перспективи розвитку. Результати – створено CI/CD рішення, що автоматизує цикл доставки, підвищує швидкість та надійність. Новизна – комплексне застосування Azure DevOps та Terraform для гнучких конвеєрів. Рекомендації – використання підходів для оптимізації розробки та експлуатації проектів. КЛЮЧОВІ СЛОВА: CI/CD, DEVOPS, AZURE DEVOPS, AZURE PIPELINES, TERRAFORM, ІНФРАСТРУКТУРА ЯК КОД, .NET CORE, АВТОМАТИЗАЦІЯ РОЗГОРТАННЯ, ХМАРНІ ТЕХНОЛОГІЇ, БЕЗПЕРЕРВНЕ РОЗГОРТАННЯ. Перелік основних використаних джерел: 1. Brikman, Y. Terraform: Up & running: Writing infrastructure as code (2nd ed.). O'Reilly Media, 2019. 2. Humble, J., & Farley, D. Continuous delivery: Reliable software releases through build, test, and deployment automation. Addison-Wesley Professional, 2010. 3. Kim, G., Humble, J., Debois, P., & Willis, J. The DevOps handbook: How to create world-class agility, reliability, & security in technology organizations. IT Revolution Press, 2016.

Object of research – CI/CD processes in the software development life cycle. The aim of the work – development and demonstration of a functional CI/CD system for automating the delivery of infrastructure and application using Azure DevOps and Infrastructure as Code. Methods – literature analysis, system analysis, technology comparison, design, modeling, implementation, testing. DevOps and CI/CD methodologies, Azure cloud technologies, Azure DevOps, and Terraform tools were analyzed. Two CI/CD pipelines were designed and implemented: for infrastructure deployment and for building/deploying a .NET Core application to different environments. Analysis of efficiency, security, and development prospects was conducted. Results – a CI/CD solution was created that automates the delivery cycle, increasing speed and reliability. Novelty – comprehensive application of Azure DevOps and Terraform for flexible pipelines. Recommendations – using the approaches to optimize project development and operations. KEYWORDS: CI/CD, DEVOPS, AZURE DEVOPS, AZURE PIPELINES, TERRAFORM, INFRASTRUCTURE AS CODE, .NET CORE, DEPLOYMENT AUTOMATION, CLOUD TECHNOLOGIES, CONTINUOUS DEPLOYMENT. List of main references used: 1. Brikman, Y. Terraform: Up & running: Writing infrastructure as code (2nd ed.). O'Reilly Media, 2019. 2. Humble, J., & Farley, D. Continuous delivery: Reliable software releases through build, test, and deployment automation. Addison-Wesley Professional, 2010. 3. Kim, G., Humble, J., Debois, P., & Willis, J. The DevOps handbook: How to create world-class agility, reliability, & security in technology organizations. IT Revolution Press, 2016.
Development and implementation of continuous integration and deployment processes for software projects
Keywords: 6.122.00.00